EVALUASI SATU DEKADE STATUS KOTA BANDUNG SEBAGAI CREATIVE CITIES NETWORK - Syatika, Okta (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
The study was to evaluate Bandung's ten-year trip as a member of the UNESCO creative cities network (uccn) in design categories. The main focus is focused on how implementation of the uccn program impacts the social, economic, and cultural development of the city, and how city branding's strategy is used in the framework of city paradiplomisation. The writer's approach used was quality-descriptive with case study methods. Data collection is carried out through deep interviews with local actors, such as academics, creative communities, and stakeholders from the bandung creative city forum (BCCF). Analysis in this study USES city branding theory and the concept of subnational paradiplomation. Research indicates that the status of a bandung creative city was not only symbolic, but it resulted in a practice of concretive collaboration across sectors. Bandung's creative hub and community initiative are boosters of local creative ecosystems. However, there are also the challenges of sustainability, structural support gaps, and limited global networking impacts. The study concluded that bandung's continued status as a UNESCO design city depends on the strengthening of local institutions, the aligning of city branding strategies, and the more direct development of international collaboration. Keywords: Bandung City, UNESCO Creative Cities Network, Creative Economy, City Branding, Sustainable Developments.